The Suitability of Visual Images in Baina Yadaik Arabic Textbook - Widyanti, Alya Rahma; Muta'ali, Abdul (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
This study was brought up due to 308 mismatches of images with the written vocabulary in the Baina Yadaik Arabic textbook. This research focused on the compatibility of visual images with written vocabulary. The object used was 1386 images in 8 chapters of the Baina Yadaik Arabic textbook volume 1A. Baina Yadaik Arabic book is an Arabic learning book used to help learners learn everyday vocabulary for beginners. This research used the visual representational mode theory by Kress and Van Leeuwen. The methodology of this study was a descriptive qualitative with multimodal discourse analysis. The VGG Image Annotator corpus tools assisted this research to analyze images with written vocabulary. This study concluded that visual images are one of the essential components of learning Arabic. Many images in Baina Yadaik Arabic textbook volume 1A do not match the written vocabulary. This book still adheres to Arabic culture, which is very different from the culture in Indonesia, and needs special attention for teacher to use this book as a learning tool.